PENGARUH TINGKAT FINANCIAL LITERACY, FINANCIAL BEHAVIOR, DAN KECERDASAN INTELEKTUAL TERHADAP KEPUTUSAN INVESTASIDIMASA PANDEMI COVID-19 - Wirawati, Ni Gusti Putu; Asri Dwija Putri, I Gusti Ayu Made (E-Jurnal Ekonomi dan Bisnis Universitas Udayana, 2024)
This study aims to determine the effect of financial literacy, financial behaviour, and intellectual intelligence on investment decisions. The population in this study were members of the Capital Market Study Group (KSPM) Udayana University 116 members. The number of samples in this study were 90 respondents calculated based on the Slovin formula. The sample technique used is simple random sampling technique, so that sampling is done randomly without regard to the criteria in the population. The data collection method in this study used a questionnaire distributed to respondents of Udayana University KSPM members. The data analysis technique used is multiple linear regression analysis and uses the SPSS program as an analysis tool. The results of this study indicate that financial literacy and financial behaviour have a positive effect on investment decisions, but intellectual intelligence has no effect on investment decisions.